THE ROLE OF THE SCHOOL COMMITTEE IN IMPROVING SCHOOL EFFECTIVENESS AND THE PERFORMANCE OF JUNIOR HIGH SCHOOL PRINCIPLES IN ACEH TAMIANG REGENCY - Aini Safitri; Ahmad Fauzi (The Islamic Education and Multiculturalism Foundation, 2022)
Principals have a strategic position in realizing quality school committees. The level of participation of the community, parents/guardians, and low school committees, was promoted by the principal as a driving force with the principle of mutual cooperation Mutual cooperation (Gotong Royong). The principal must have straight intentions, be generous, dedicated, and obey the rules. School committees, they are selected and carry out functions according to Minister of Education and Culture Regulation number 75 of 2016, become quality school committees. The collaboration of school principals with quality school committees improves the quality of education services. The school principal must strive to be the driving force for the re-election of the school committee with the guidelines of Minister of Education and Culture Regulation number 75 of 2016. The quality of education services is a shared responsibility, parents/guardians of students, the community, school committees, teachers, education staff, and all parties to work together increase their participation. The school committee is an independent institution that accommodates community participation consisting of people who care about education, formed and playing a role in efforts to improve the quality, equity and efficiency of education management and provide consideration, direction, support and supervision at the school level.